At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
First Solution
-2x + y = 1
-2x + 2x + y = 1 + 2x
y = 1 + 2x
Second Solution
-2x + y = 1
-2x + y - y = 1 - y
-2x = 1 - y
-2 -2
x = -0.5 + 0.5y
0.5 + x - x = -0.5 + 0.5 - x + 0.5y
0.5 = -x + 0.5y
-0.5y - 0.5 = -x + 0.5y - 0.5y - 0.5
2 · (-0.5y) = 2(-x - 0.5)
y = -2x - 1
Third Solution
-2x + y = 1
-2x + y - 1 = 1 - 1
-2x + y - 1 = 0
-2x + 2x + y - 1 = 2x
y - 1 = 2x
y - 1 + 1 = 2x + 1
y = 2x + 1
-2x + y = 1
-2x + 2x + y = 1 + 2x
y = 1 + 2x
Second Solution
-2x + y = 1
-2x + y - y = 1 - y
-2x = 1 - y
-2 -2
x = -0.5 + 0.5y
0.5 + x - x = -0.5 + 0.5 - x + 0.5y
0.5 = -x + 0.5y
-0.5y - 0.5 = -x + 0.5y - 0.5y - 0.5
2 · (-0.5y) = 2(-x - 0.5)
y = -2x - 1
Third Solution
-2x + y = 1
-2x + y - 1 = 1 - 1
-2x + y - 1 = 0
-2x + 2x + y - 1 = 2x
y - 1 = 2x
y - 1 + 1 = 2x + 1
y = 2x + 1
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.